Investigation of ACE-overexpression in Myeloid Cell Lines through Whole-Proteome Analysis - Batteson, Delia (Department of Psychiatry and Mental Health, 2024)
Abstract Angiotensin converting enzyme (ACE) plays an important role in blood pressure regulation and is a key component of the renin-angiotensin aldosterone system (RAAS). A dipeptidyl carboxypeptidase, ACE also hydrolyses many different substrates across its N- and C-domain. This substrate variability has uncovered novel ACE function in other biological systems and disease. In the immune system, ACE and angiotensin II influence inflammation and wound repair. Independently of angiotensin II, ACE overexpression in murine macrophages (ACE 10/10) and neutrophils (NeuACE) has shown remarkable enhanced immune phenotypes with the ability to improve murine survival against B16 melanoma, methicillin-resistant Staphylococcus aureus (MRSA) and Listeria monocytogenes. Current literature points to the C-domain as the main proponent. The myeloid cells have enhanced reactive oxygen species (ROS) generation, pro-inflammatory cytokine production and phagocytosis with increased ATP and TCA cycle intermediate production. ACE overexpressing macrophages also improve cognitive ability in murine Alzheimer's models by amyloid-β (1-42) protein cleavage and degradation. Despite lengthy characterization of ACE overexpression and the enhanced immune phenotype of ACE 10/10 macrophages and NeuACE neutrophils, the mechanism, and substrate(s) by which it occurs is unknown. Understanding the biological processes influenced by ACE overexpression may provide alternative therapies where standard medicine is no longer effective including resistant bacterial infections and tumours. Importantly, ACE inhibition in human and murine neutrophils, and ACE 10/10 macrophages has shown reduced extracellular and intracellular microbicidal function. This and the immune benefit associated with ACE overexpression has prompted interest in the mechanism responsible. This project aimed to identify differentially expressed and significantly dysregulated biological pathways and proteins in ACE overexpressing murine (ACE 10/10 PTM) and human macrophages (ACE +/+ THP-1) whilst also analysing global proteomic changes with respects to ACE inhibition using discovery mass spectrometry (MS). ACE overexpressing murine and human macrophage whole cell protein lysates underwent label-free discovery MS to identify proteomic shifts in comparison to control macrophages. Using data-independent methodology, 270 and 442 differentially expressed proteins were identified in murine and human ACE overexpressing macrophages, respectively. Functional enrichment for several immune processes including phagocytosis, ROS generation, and antigen processing and presentation were identified whilst metabolic enrichment for TCA, fatty acid oxidation, electron transport chain (ETC) and glucose was present in murine ACE 10/10 macrophages. Human ACE +/+ THP-1 macrophages saw similar ETC, ATP synthase and glucose protein up-regulation and cytokine signalling, antigen processing and presentation functional enrichment. Unique to ACE +/+ human macrophages was neutrophil degranulation whereupon ACE C-domain inhibition by Lis-Trp dysregulated these proteins. Both murine and human ACE overexpression identified KEGG peroxisome proliferator-activated receptor (PPAR) signalling as significantly enriched, providing a possible target pathway for future mechanistic validation studies. ACE C-domain inhibition following Lis-Trp treatment led to a general downregulation of the functionally enriched ETC, TCA and ATP synthase components identified as up-regulated in the literature and our own murine MS results. Murine phosphoproteomic analysis identified ERK2/MAPK1 and PKA kinase-substrate enrichment with ACE overexpression. Using the human cell line, THP-1, Lis-Trp uptake was quantified through MS and ACE enzymatic activity assays over two hours. Minimal internalization took place for both 10 µM and 100 µM with < 1% intracellular Lis-Trp detected. However, partial ACE inhibition was achieved for both treatments despite low intracellular concentrations. To study the impact of this partial inhibition, the role of ACE in phagocytosis was explored. Using elastomeric micropattern contraction as a proxy for phagocytic uptake, ACE C- and N-domain inhibition both led to significant reduction in micropattern contraction in comparison to uninhibited control THP-1 macrophages. ACE +/+ THP-1 macrophages showed enhanced phagocytosis as observed in murine ACE 10/10 macrophage literature by means of increased micropattern contraction. Following ACE domain inhibition by 10 µM Lis-Trp (C-domain) and 10 µM RXP407 (N-domain) a statistically significant decrease in contraction measurements was observed, implying that both the N- and C-domain of ACE play a role in phagocytosis. Partial ACE inhibition may therefore be sufficient in reducing macrophage microbicidal function as observed in NeuACE and human neutrophils, increasing the potential risk of dangerous infection in immunocompromised patients. This work demonstrated an altered proteomic profile in ACE overexpressing murine and human macrophages, and confirmed findings on ACE 10/10 murine macrophages, whilst providing a novel and deeper understanding of ACE +/+ human macrophages. Furthermore, ACE C-domain inhibition likely negatively impacts macrophage function including phagocytosis whilst increasing neutrophil degranulation, but further biochemical characterization is required. Importantly, novel lipid metabolism and PPAR signalling were functionally enriched in both species, providing an exciting path for future studies in ACE overexpression and enhanced immunity.